2008
DOI: 10.1111/j.1365-2672.2008.03954.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of culturable enteroviruses in wastewater and surface waters of north-eastern Spain

Abstract: Aims:  Update information regarding occurrence and levels of culturable enteroviruses in several types of surface polluted waters in north‐eastern Spain and determine the proportion of the different species and serotypes. Methods and Results:  The best procedures on hand in our laboratory for concentrating and quantifying culturable enteroviruses from different water sample types were used. Sequencing was used for typing the virus isolates. Geometric means of enteroviruses densities expressed in plaque forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 44 publications
6
16
2
2
Order By: Relevance
“…In contrast, only a few recent investigations have been performed using detailed serotyping of enterovirus strains in Italian wastewaters (32,33,34,52) compared to a higher number of similar studies reported from other countries (53,54,55,56,57,58).…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, only a few recent investigations have been performed using detailed serotyping of enterovirus strains in Italian wastewaters (32,33,34,52) compared to a higher number of similar studies reported from other countries (53,54,55,56,57,58).…”
Section: Discussionmentioning
confidence: 93%
“…Environmental surveillance in Greece revealed echoviruses to be the most frequently isolated, followed by CVBs. CVBs have generally been reported to be the most frequently isolated EVs from environmental samples worldwide (25)(26)(27). It is noteworthy that of the 26 EV serotypes isolated from stool samples, only six were detected in sewage water samples, all belonging to species B.…”
Section: Discussionmentioning
confidence: 99%
“…This sludge contains enteric pathogens and needs to be properly treated for recycling or disposal (discussed below in Section III). Multiple levels of wastewater treatment (preliminary, primary, secondary, and tertiary or advanced) and combination of their corresponding treatment technologies are required to consistently reduce, remove and/or inactivate the vast numbers of viruses present in all the wastes sent into the sewer from drains and toilets (Costan-Longares et al, 2008;Haramoto and Otagiri, 2013;Harwood et al, 2005;Hegazy et al, 2013;Katayama et al, 2008;Kitajima et al, 2014a; Rock et al, 2015;Simmons and Xagoraraki, 2011a;Symonds et al, 2014). The greater the exposure of the public to these contaminated sources, the greater the need for treatment to reduce all viral pathogens and hazardous contaminants present in these wastes (Gerba et al, 2013;Rock et al, 2015;Xagoraraki et al, 2014).…”
Section: Hygiene Measuresmentioning
confidence: 99%